Identification and characterization of the cytochrome p450 complement in Streptomyces cavourensis YBQ59 - Quach, Ngoc Tung; Vu, Thi Hanh Nguyen; Nguyen , Thi Mai Phuong; Phi , Quyet Tien; Ly, Thi Bich Thuy (Vietnam Journal of Biotechnology, 2024)
Cytochrome P450 enzymes (CYPs) are regarded as some of the most versatile biocatalysts. They are attractive candidates for natural product development because of their ability to selectively oxidize a broad range of substrates. Streptomyces spp. are not only producers of biologically active secondary metabolites but also a rich source of P450 enzymes. However, only a limited number of studies have explored the function and potential of P450 enzymes encoded in the Streptomyces genomes. In this study, the endophytic Streptomyces cavourensis YBQ59 isolated from Cinnamomum cassia J. Presl was sequenced using the Illumina sequencing platform to identify its P450 enzymes. The genome of YBQ59 was approximately 8,126,002 bp in size, with a G + C content of 72.1% and contained 7,020 genes. Genome annotation identified 21 CYP genes, distributed across 10 CYP families and 17 subfamilies. The possible role of these P450 enzymes in the synthesis of secondary metabolites was discussed. Since CYPs often require electron transport proteins to function, we analyzed the physical map of the genes encoding ferredoxins and ferredoxin reductases found in the genome of S. cavourensis YBQ59. Additionally, a phylogenetic tree was constructed to compare the P450 enzyme system from S. cavourensis YBQ59 with those of closely related and well-studied Streptomyces species, including Streptomyces sp. CFMR7, S. fulvissimus DSM 40593, S. griseus IFO 13350, and S. globisporus 1912. These results provide a basis for exploiting potential P450 enzymes from S. cavourensis YBQ59 for agricultural and medicinal applications.